Basic Income Guarantee and Politics International Experiences and Perspectives on the Viability of Income Guarantee - Caputo, R.; SpringerLink (Online service) (New York : Palgrave Macmillan US : Imprint: Palgrave Macmillan, 2012)
This exciting and timely collection brings together international and national scholars and advocates to provide historical overviews of efforts to pass basic income guarantee legislation in their respective countries and/or across regions of the globe. .
Keywords: Economic policy; Macroeconomics; Political economy; International economics; Economics; Labor economics; Economic Policy; Macroeconomics/Monetary Economics//Financial Economics; International Political Economy; International Economics; Political Economy/Economic Systems; Labor Economics